A közösségfejlesztés lehetőségei a Kiskőrösi kistérségben - Panyor, Ágota (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The Great Depression has his effect felt powerfully on Hungary in our days. I believe that the community development wich one was alredy used on many fields int he world with succes might report the solution in our homeland as well. I will introduce the micro-region of Kiskőrös. The people’s living in this area gets out mainly from the agrarian section, fruits, grapes and naturelly the winery. Unfurtunately, by today considerable decline can be observed on that place. I will try to find out the real reasons, according to the community develpoments’ method I have made a research among the viticulturist int he form of oral asking.